EFEKTIVITAS WEBSITE E-LEARNING PADA PEMBELAJARAN SEJARAH SMK N 1 DAYUN DI MASA PANDEMI COVID-19 - Prayoga, Ari; Situmorang, Ideal; Ramandha, Levyance; Parman, Parman; Ahmal, Ahmal (STKIP Pesisir Selatan, 2021)
This study aims to determine the effectiveness of the e-learning website in history learning at SMK N 1 Dayun during the covid-19 pandemic. This type of research is descriptive. The research subject is SMKN 1 Dayun. Data collection techniques were carried out by interview, observation and documentation. The results of this study are the application of website-based e-learning learning for history subjects at school with an online or online system during the Covid-19 pandemic, making it easier for students to access subjects, assignments and a lot of other information in the form of announcements. entered and by the teacher in the e-learning website, so that students can access it easily, anytime, anywhere. All materials, assignments and announcements are input by the teacher into the e-learning system. Through this system, an additional learning interaction between teachers and students will be formed from face-to-face interactions in the classroom. The use of websites in the learning process can make it easier for students to carry out teaching and learning activities and can improve the quality of education at SMK N 1 Dayun.